Analysis of HIV and syphilis transmission prevention programs: how to implement for adolescents? - Yusuf Hanafi Lubis; Susilawati (Social Medicine Publication Group, 2023)
Objectives: Adolescents tend to want to try everything that they have not yet experienced. The main factor that causes this is curiosity about what adults do, including sexuality. The aim of this study is to analyze HIV and syphilis transmission programs for adolescents in North Sumatra. Methods: We used a cross-sectional design analytical survey by taking 729 people as a sample of the total adolescent population of around 19.4%. Non-random tools and interview materials using questionnaires adopted from The Prospero Network were made through an online platform. Then the results were transferred into a statistical-based application for descriptive data analysis and bivariate (chi square) and multivariate statistical tests (multiple logistic regression).  Results: We found that less than 50% of respondents conducted HIV and Syphilis free examinations through the laboratory and reactive confirmation tests through health facilities. Statistical test results showed that all variables were related and the risk to be up to 160.7 times in bivariate and 176.3 in multivariate. Conclusion: Not conducting HIV and Syphilis transmission prevention programs for adolescents entails a high risk, and the government and community must work together so that these programs always run well. Keywords: adolescents, health program, HIV, syphilis.